Effectiveness of Advance Care Planning Group Visits Among Older Adults in Primary Care. Issue 10 (29th July 2020) - Lum, Hillary D.; Dukes, Joanna; Daddato, Andrea E.; Juarez‐Colunga, Elizabeth; Shanbhag, Prajakta; Kutner, Jean S.; Levy, Cari R.; Sudore, Rebecca L.
Abstract : BACKGROUND: Group visits can support health behavior change and self‐efficacy. In primary care, an advance care planning (ACP) group visit may leverage group dynamics and peer mentorship to facilitate education and personal goal setting that result in ACP engagement. OBJECTIVE: To determine whether the ENgaging in Advance Care Planning Talks (ENACT) group visits intervention improves ACP documentation and readiness in older adults. METHODS: This randomized clinical trial was conducted among geriatric primary care patients from the University of Colorado Hospital Seniors Clinic, Aurora, CO, from August 2017 to November 2019. Participants randomized to ENACT group visits (n = 55) participated in two 2‐hour sessions with discussions of ACP topics and use of ACP tools (i.e., Conversation Starter Kit, Medical Durable Power of Attorney form, and PREPARE videos). Participants randomized to the control arm (n = 55) received the Conversation Starter Kit and a Medical Durable Power of Attorney form by mail. The primary outcomes included presence of ACP documents or medical decision‐maker documentation in the electronic health record (EHR) at 6 months, and a secondary outcome was ACP readiness (validated four‐item ACP Engagement Survey) at 6 months. RESULTS: Participants were a mean of 77 years old, 60% female, and 79% white. At 6 months, 71% of ENACT participants had an advance directive in the EHR (26% higher) compared with 45% of control arm participants ( P < .001). Similarly, 93% of ENACT participants had decision‐maker documentation in the EHR (29% higher) compared with 73% in the control arm ( P < .001). ENACT participants trended toward higher readiness to engage in ACP compared with control (4.56 vs 4.13; P = .16) at 6 months. CONCLUSION: An ACP group visit increased ACP documentation and readiness to engage in ACP behavior change. Primary care teams can explore implementation and adaptation of ACP group visits into routine care, as well as longer‐term impact on patient health outcomes. J Am Geriatr Soc 68:2382–2389, 2020.